A Pilot Study: Changes of Intestinal Microbiota of Patients With Non-small Cell Lung Cancer in Response to Osimertinib Therapy - Cong, Jing; Zhang, Yuguang; Xue, Yadong; Zhang, Chuantao; Xu, Mingjin; Liu, Dong; Zhang, Ruiyan; Zhu, Hua (Frontiers in Microbiology, 2020)
Osimertinib contributes to the higher efficacy and few intestinal side effects in non-small cell lung cancer (NSCLC) patients with T790M mutation. Previous studies has reported that intestinal microbiota play important roles in drug efficacy and toxicity. However, we have known less about the changes of intestinal microbiota in response to osimertinib therapy. In this pilot study, we used longitudinal sampling with six weeks sampling collection intervals for about one year to model intestinal microbial changes based on the 16S rRNA genes sequencing in fecal samples from NSCLC patients in response to osimertinib therapy. The results showed that there was no significantly different on the intestinal microbial composition at the phylum, family, and genus level among NSCLC patients with different treatment cycles (P > 0.05). There were no significant differences in alpha diversity characterized by the richness, Shannon diversity, and phylogenetic diversity based on the Welch’s test among NSCLC patients in response to osimertinib therapy (P > 0.05). However, the dissimilarity test and principal coordination analysis showed a few differences among NSCLC patients. The intestinal microbial markers were changed in post-therapy (Sutterella, Peptoniphilus, and Anaeroglobus) compared to that in pre-therapy (Clostridium XIVa). Furthermore, the phylogenetic molecular ecological networks were influenced by osimertinib therapy based on the module number, link number, and module taxa composition of the first six groups. Overall, it indicated that osimertinib therapy changed the intestinal microbiota to some extent, though not completely. In all, this pilot study provides an understanding of changes of intestinal microbiota from NSCLC patients in response to osimertinib therapy. No complete changes in intestinal microbiota seem to be closely linked with the few intestinal side effects and higher efficacy in response to osimertinib therapy.